Data Stream Segmentation Apparatus and Method For Activity Prediction - LEE, YOUNG HEE; CHO, HYUN JEONG; HONG, IN TAEK; AN, JI HOON (2017)
The present invention relates to a device and a method for automatically splitting data streams. The device for automatically splitting the data streams comprises: a window generating unit; a database; an activity inference engine; and a similarity measuring unit. The window generating unit enables an external device for measuring a subject to receive a series of data generated depending on an operation of the subject; and designates first data among the series of the data as a window starting point which is the standard of splitting the data streams. The database matches a window consisting of predetermined data arrays and specific activities of the subject; and stores the same. The activity inference engine compares the series of the data with the window stored in the database; and infers the activities of the subject. When the activities of the subject are inferred, the similarity measuring unit measures a similarity between the window and the series of the data in the database matched with the inferred activities. The window generating unit designates a data point with the maximal similarity as a window ending point; and stores data streams from the window starting point to the window ending point in the database as the window matched with the inferred activities. The present invention splits the data streams measured through a sensor for accurate activity analysis and activity prediction into an activity unit of the subject by oneself; and digitizes the data streams in the database. 본 발명은 데이터 스트림 자동 분할 장치 및 방법에 관한 것으로서, 보다 상세하게는 피사체를 관측하는 외부장치가 피사체의 동작에 따라 생성한 일련의 데이터를 입력받고, 일련의 데이터 중 첫번째 데이터를 데이터 스트림을 구분짓는 기준인 윈도우 시작점으로 지정하는 윈도우 생성부; 기 지정된 데이터 배열로 구성된 윈도우와 피사체의 특정 활동을 매칭시켜 저장하고 있는 데이터베이스; 일련의 데이터를 데이터베이스에 저장된 윈도우와 비교하여 상기 피사체의 활동을 추론하는 활동 추론 엔진; 및 피사체의 활동이 추론된 경우, 추론된 활동과 매칭되어 있는 데이터베이스 상의 윈도우와 상기 일련의 데이터 간 유사도를 측정하는 유사도 측정부;를 포함하고, 상기 윈도우 생성부는, 유사도가 최대인 데이터 지점을 윈도우 종결점으로 지정하고, 윈도우 시작점부터 상기 윈도우 종결점까지의 데이터 스트림을 상기 추론된 활동과 매칭된 윈도우로서 데이터베이스에 저장하는 것을 특징으로 한다. 따라서 본 발명에 따르면, 정확한 활동 분석과 활동 예측을 위해 센서를 통해 측정된 데이터 스트림을 피사체의 활동 단위로 스스로 분할하고 데이터베이스화할 수 있다.